Identification and partial characterisation of the HSP70 gene of the South African abalone Haliotis midae - Lyons, Jarrod (Department of Molecular and Cell Biology, 2015)
Identifying genes which are up-regulated in response to stress has become important in understanding invertebrate immunity. The HSP70 gene from Haliotis midae was successfuly cloned and sequenced, and was found to have highest similarity (99%) with Haliotis diversicolor.